Generalized Tonic-Clonic Seizures after Self-Limited Epilepsy with Centrotemporal Spikes: A Case Series - Hye Jin Kim; Young Joon Ko; Soo Yeon Kim; Anna Cho; Hunmin Kim; Byung Chan Lim; Hee Hwang; Jong-Hee Chae; Jieun Choi; Ki Joong Kim (Korean Child Neurology Society, 2022)
Purpose Patients with self-limited epilepsy with centrotemporal spikes (SLECTS) rarely experience generalized tonic-clonic seizures (GTCS) after remission, and post-remission GTCS has not been thoroughly described in earlier studies. Herein, we describe the clinical and electrographic features of GTCS after a substantial period of seizure freedom in patients with SLECTS. Methods This study included six patients (three boys and three girls) diagnosed with SLECTS who later developed GTCS after or near remission. Medical records, including clinical data and serial electroencephalography (EEG) recordings, were retrospectively reviewed for all patients. Results Patients' age at SLECTS onset ranged from 5.2 to 10.2 years (mean, 8.4 years), while seizure cessation was achieved between 8 and 12.2 years. During SLECTS, typical centrotemporal spikes were observed in all patients, and generalized spike-and-wave discharges were observed in three patients. The age at the first episode of subsequent GTCS ranged from 14.4 to 17.3 years (mean, 15.8 years), constituting an average interval of 5.6 years after the last episode of seizures (range, 4.1 to 8.1 years). EEG at subsequent episodes of GTCS revealed generalized discharges in two patients, focal discharges in two other patients, and normal discharges in the remaining two patients. Two patients had multiple episodes of GTCS. Conclusion Although rare, GTCS may occur near or after remission in patients with SLECTS, and clinicians should be aware of this. Subsequent GTCS may be a manifestation of idiopathic generalized epilepsy. However, large-scale studies are needed to determine the nature of such episodes of GTCS and their associated risk factors.